Exploring Islamic Vision on the Environmental Architecture of Traditional Javanese Landscape: Study of Thematic Tafseer Perspective - Lukman Fajariyah; Abd Halim; Nur Rohman; Mokhamad Zainal Anwar; Abraham Zakky Zulhazmi (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
This article examines and explores Islamic visions of environmental architecture and traditional Javanese houses (joglo) from the Qur'anic perspective. This qualitative research with a descriptive method seeks to analyse the values and Islamic vision of the Joglo house architecture by exploring several data sources, both field data and literature data. The results of this study indicate that the architectural elements of the joglo house contain philosophical ideas that are relevant to the Islamic visions in the Qur'an, such as; pendapa (containing the philosophical meaning of the openness principle), pringgitan (principle of equality), dalem (principle of privacy), senthong (principle of respect), gandok (principle of food security), and pawon (use of firewood) as for the suitability of philosophical ideas with the Islamic vision in the architectural elements of the environment, namely sawo (containing the philosophical meaning of the goodness principle), jambu dersono (the principle of sharing), belimbing lingsir (the principle of remembering God), papaya (the principle of self-introspection), and beringin (the principle of knowing the origin). In short, the joglo house building reflects a house that can adapt to the environment and nature. Therefore, joglo is a representation of house architecture that can combine natural elements that are outward and inward, thus creating a comprehensive and balanced religious value.